Diabetes-Related Ankyrin Repeat Protein (DARP/Ankrd23) Modifies Glucose Homeostasis by Modulating AMPK Activity in Skeletal Muscle - Shimoda, Yoshiaki; Matsuo, Kiyonari; Kitamura, Youhei; Ono, Kazunori; Ueyama, Tomomi; Matoba, Satoaki; Yamada, Hiroyuki; Wu, Tongbin; Chen, Ju; Emoto, Noriaki; Ikeda, Koji (PLOS ONE, 2015)
Skeletal muscle is the major site for glucose disposal, the impairment of which closely associates with the glucose intolerance in diabetic patients. Diabetes-related ankyrin repeat protein (DARP/Ankrd23) is a member of muscle ankyrin repeat proteins, whose expression is enhanced in the skeletal muscle under diabetic conditions; however, its role in energy metabolism remains poorly understood. Here we report a novel role of DARP in the regulation of glucose homeostasis through modulating AMP-activated protein kinase (AMPK) activity. DARP is highly preferentially expressed in skeletal muscle, and its expression was substantially upregulated during myotube differentiation of C2C12 myoblasts. Interestingly, DARP-/- mice demonstrated better glucose tolerance despite similar body weight, while their insulin sensitivity did not differ from that in wildtype mice. We found that phosphorylation of AMPK, which mediates insulin-independent glucose uptake, in skeletal muscle was significantly enhanced in DARP-/- mice compared to that in wildtype mice. Gene silencing of DARP in C2C12 myotubes enhanced AMPK phosphorylation, whereas overexpression of DARP in C2C12 myoblasts reduced it. Moreover, DARP-silencing increased glucose uptake and oxidation in myotubes, which was abrogated by the treatment with AICAR, an AMPK activator. Of note, improved glucose tolerance in DARP-/- mice was abolished when mice were treated with AICAR. Mechanistically, gene silencing of DARP enhanced protein expression of LKB1 that is a major upstream kinase for AMPK in myotubes in vitro and the skeletal muscle in vivo. Together with the altered expression under diabetic conditions, our data strongly suggest that DARP plays an important role in the regulation of glucose homeostasis under physiological and pathological conditions, and thus DARP is a new therapeutic target for the treatment of diabetes mellitus.